The Role of Banking in Achieving Sustainability Development Goals 8 - Majidah Majidah; Angela Paskah Maria Hutagaol (International Journal of Economics Development Research (IJEDR), 2024)
The Sustainability Development Goals are global sustainable ideas planned to be achieved by 2030. One of the goals of concern to the world today is economic growth. A country's economic growth can be achieved by strengthening the micro economy. Banking, with its intermediary institution function and the motor and stabilizer of the economy, can be one of the country's partners in achieving a strong and growing microeconomy. Therefore, this study aims to analyze the factors that have the potential to strengthen the banking function to achieve economic growth. Some of the factors examined are using corporate governance measured by the ASEAN Corporate Governance Scorecard as one of the assessments, gender diversity, profitability ratios such as net interest margin, non-performing loans, and audit quality. The object of this research is banking listed on the Indonesia Stock Exchange (IDX) for 2019-2022. A sample of 35 companies or 140 observation data was obtained with purposive sampling. The research data were analyzed using panel data regression. The results showed that the ASEAN Corporate Governance Scorecard had a negative effect on SDGs-8 and gender diversity positively affected SDGs-8. The results of this study are also research findings for banks listed on the IDX. The limitation of this study is the difficulty of accessing information on the ACGS score of each bank in Indonesia. Future research should use corporate governance proxies with other corporate governance assessment models. For companies, the results of this study can be used as evaluation material for improvement.